Breast ultrasound with elastography reduces the number of unnecessary biopsies (Texas Journal of Medical Science, 2024)
Ultrasound elastography (USE) is a tissue-stiffness-sensitive imaging technology that was first described in the 1990s. In recent years, it has been refined and refined to provide a quantitative assessment of tissue stiffness. Elastography techniques use altered elasticity of soft tissues as a result of certain pathological or physiological processes. For example, it is known that many solid tumors are mechanically distinct from the surrounding healthy tissues. Similarly, fibrosis associated with chronic liver disease causes the liver to become stiffer than normal tissue. Thus, elastography techniques can be used to differentiate diseased tissues from normal tissues for diagnostic purposes.